Validity of Chemiluminescent Immunoassay Serology Test for Anti-Sars Cov-2 Antibodies IgM and IgG 1 - Museyaroh Museyaroh; Puspa Wardhani; Aryati Aryati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
In December 2019, an outbreak of acute pneumonia occurred in Wuhan, China. The disease was transmitted betweenhumans through droplets (coughing or sneezing) of infected patients, causing this outbreak to spread rapidly in variouscountries in the world, including Indonesia. On February 11, 2020, WHO announced the pneumonia was caused byCoronavirus Disease 2019 (COVID-19), which was caused by a new type of Coronavirus, the SARS-CoV-2. A rapid andaccurate diagnosis is critical for the control of the COVID-19 outbreak. The widely used test is a serology-based test thatdetects the presence of SARS-CoV-2 IgM/IgG antibodies in the patient's body. One of the methods used for this test isChemiluminescent Immunoassay (CLIA). This study aimed to determine the reliability of CLIA. The study was conductedfrom August to September 2020. The number of samples was 63 patients' serum. Polymerase chain reaction examination atHusada Utama Hospital, Surabaya, revealed that 21 patients were confirmed positive for COVID-19 with positive PCRresults, and 42 patients were healthy with negative COVID-19 results. The results showed that IgM had a diagnosticsensitivity of 85.7%, diagnostic specificity of 92.8%, a positive predictive value of 85.7%, a negative predictive value of 92.8%,and accuracy of 90.4%. In comparison, IgG had a diagnostic sensitivity of 90.4%, diagnostic specificity of 90.4%, a positivepredictive value of 82.6%, a negative predictive value of 90.5%, and accuracy of 90.4%. In conclusion, IgG has a highersensitivity than IgM, while IgM had higher specificity, positive predictive value, and negative predictive value than IgG.However, the positive, negative predictive value and efficiency values were the same for IgM and IgG.